The complete mitochondrial genome and phylogenetic analysis of Lotus corniculatus (Fabaceae, Papilionoideae) - Chen, Xiaofei; Wu, Zinian; Yang, Yanting; Tao, Qibo; Na, Na; Wan, Wenya; Tian, Chunyu; Gong, Wenlong; Li, Zhiyong (Frontiers in Plant Science, 2025)
IntroductionLotus corniculatus is a perennial leguminous herb and serves as a high-quality forage, playing a key role in both grassland ecological restoration and the development of grazing livestock farming.MethodsIn this study, we successfully assembled the L. corniculatus mitochondrial genome and investigated various related aspects, including genomic features, RNA editing sites, codon preference, gene transfer events, and phylogeny.Results and discussionWe found that the length of the L. corniculatus mitochondrial genome is 401,301 bp, and its GC content is 45.15%. It consists of 53 genes, comprising 32 protein-coding genes, 3 ribosomal RNA genes, and 18 transfer RNA genes. A total of 146 scattered repeats, 8 tandem repeats, and 124 simple sequence repeats are present in the mitochondrial genome. A thorough examination of all protein-coding genes revealed 485 instances of RNA editing and 9579 codons. Additionally, 57 homologous fragments were identified in L. corniculatus mitochondrial genome and chloroplast genomes, accounting for approximately 4.04% of the L. corniculatus mitochondrial genome. Furthermore, a phylogenetic tree based on mitochondrial genome data from 33 species belonging to four Fabaceae subfamilies and two species from other families validated the evolutionary relationship of Lotus. These findings have significant implications for understanding the organization and evolution of the L. corniculatus mitochondrial genome as well as for the identification of genetic markers. They also offer valuable perspectives relevant to devising strategies for molecular breeding and evolutionary categorization of legumes.